Gestión de recursos financieros y su influencia en los logros de los objetivos estratégicos en instituciones educativas secundarias de la zona urbana de Iquitos 2022 - Ramirez Ramirez, Dianit (2025)
The primary goal of this study was to provide light on how the management of financial resources affects the attainment of strategic objectives in urban secondary schools in the Iquitos metropolitan region in the year 2022. The study's methodology was modern, univariate, quantitative, and of the explanatory type with a field design. There were 869 total participants, and 138 instructors from 15 different secondary schools in the Iquitos metropolitan region were selected for the study. For data collection, the survey was used as a technique and the questionnaire as an instrument. The most important results show that at an error level of 0.0%, the Management of Financial Resources has a very strong correlation with the achievement of the Strategic Objectives (0.971) in the Secondary Educational Institutions of the urban area of the city of Iquitos 2022. At the 95% confidence level, the research hypothesis may be acknowledged: “There is a substantial relationship between the management of financial resources and the accomplishment of strategic objectives at secondary educational institutions located in the urban region of the city of Iquitos, 2022.”